Vocación quirúrgica - Perales Cabrera, Alberto (2015)
Objective. To describe and delimit the surgical vocation process and associated factors. Design. Selected cases cross-sectional study qualitatively and quantitatively analyzed with descriptive purpose. Methods. Previous informed consent in depth audio-recorded interviews was carried out in 40 surgeons in current professional practice. Main outcome measures. Surgical vocation. Results. Males represented 95%; mean age was 65 years (41-86), mean medical experience 35.4 years (10-68), surgical experience 30.2 years (03-59). Training centers: 85% had university surgical training and 15% non-university training. Surgical vocation is a process that can begin in different periods of the life`s cycle. When it does before university studies (17.5% of the studied sample) it is mainly associated to strong family influence (parents or uncles surgeons). More frequently (80%) it emerges during medical undergraduate studies, under the influence of diverse formative stimuli provided by the medical school and/or paradigmatic professors. In one case (2.5%) surgical vocation had emerged at an early age whose origin the interviewed could not explain. Conclusions. Surgical vocation is based on solid service vocation. The surgeon with substantive vocation experiences real pleasure in doing surgical activities being oriented to a comprehensive and ethical management of patient and family. Finally, new research hypothesis produced by this study in this area are discussed and recommendations are given for professional teaching of surgery including Ethics as a basic need in surgeon´s training.